Are quantity and content of psychiatric interventions associated with suicide? A case-control study of a Swedish sample - Fredrik Holländare; Maria Tillfors; Axel Nordenskjöld; Tabita Sellin (BMC Psychiatry, 2020)
Abstract Background Research is required to identify those psychiatric interventions with a protective effect against suicide. The overarching aim of the current study was to examine whether completed suicide in psychiatric patients in a Swedish population was associated with the quantity and nature of previous medical and psychosocial treatment interventions. Methods This retrospective case-control study (n = 308) compared a group of deceased psychiatric patients with matched controls. For every case of suicide, a control was found within psychiatry that matched according to sex, age, and primary psychiatric diagnosis. A stepwise forward logistic regression model with suicide as the dependent outcome variable was used. Results Receiving pharmacotherapy combined with psychotherapy [OR: 0.44 (95% CI: 0.226–0.876), p = 0.019] and a higher number of outpatient visits in psychiatry [OR: 0.99 (95% CI: 0.982–0.999), p = 0.028] were negatively associated with suicide. These associations were still significant after controlling for previous serious suicide attempts and somatic comorbidity. Conclusions Frequent visits and pharmacotherapy combined with psychotherapy seem to be important for preventing suicide in psychiatric patients. The reasons for not receiving such therapy are important issues for further study.